Justice in conflict : the effects of the International Criminal Court's interventions on ending wars and building peace - Kersten, Mark (Oxford : Oxford University Press, 2016)
It has been said that we no longer consider whether to pursue justice, but how and when. Justice no longer follows in the wake of peace; it is pursued while violent political conflicts are on-going. This book explores the relationship between peace and justice through an analysis of the interventions of the ICC into on-going and active conflicts.
This edition also issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 14, 2016).
Keywords: International courts; Conflict management; Justice; Peace; International Criminal Court; Law; International law